Time domain computer simulation and its applications to transient EMC problems and VLSI interconnection systems. - Cai, Xiao-Ding. (University of Ottawa (Canada), 1995)
The time domain computer simulation presented in this Ph.D. thesis is composed of three parts. The first part is an introduction of a novel finite element formulation in the Laplace domain and its applications to the technical area of electromagnetic compatibility (EMC). The second part presents a new time domain resistance (skin effect) model and its applications to the analysis of VLSI interconnection systems. The applications include two topics: time domain analysis of lossy VLSI interconnects with a time domain skin effect model; and time domain analysis of interconnect discontinuities. In the last part of this thesis, a numerical modelling approach of the partial inductance, which is of great importance in ground noise problems, is provided. All the analysis models in this thesis are finalized in the time domain, though some of them start in the Laplace domain or space domain. Original contributions are summarized in Section 1.3.
Keywords: Engineering, Electronics and Electrical.